‘Friendship’ takes audience down memory lane of their school days - Nurizzati, Md Tuhidin (2018)
Waris Theatre Club staged a play titled, ‘Friendship’ which was about friendship among five students from Cempedak Class of Sekolah Menengah Kebangsaan Warisan and the conflicts they had with their teachers.